AUDIT MANAJEMEN ATAS FUNGSI KEUANGAN PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA ANOA KENDARI - Rimporok, Ch.; Safaruddin, Safaruddin; M, Andi Trisno (JURNAL AKUNTANSI DAN KEUANGAN, 2017)
The purpose of this study was to determine the systems and procedures for financial functions at the Regional Water Company (PDAM) Tirta Anoa Kendari were run effectively and efficiently.The method used is using descriptive analysis that provides an explanation of the efficiency and effectiveness of the finance function and findings obtained based on the results of audits at the Regional Water Company (PDAM) Tirta Anoa Kendari, then make recommendations to the top management on these findings.The result showed that the company already has an organizational structure, division of tasks and responsibilities are clear and sufficient. The the existing shortcomings in the company is the financial part not prepare cash flow, the concurrent positions in the finance function, there is no adequate employee training, as well as the absence of rotation of employees.Keyword: Management Audit, Finance Function, Efficiency and Effectivenes.